In vitro activity of ketoconazole against herpes simplex virus. - Pottage, J C (1986)
The effects of ketoconazole alone and in combination with acyclovir and adenine arabinoside upon the replication of herpes simplex virus types 1 and 2 (HSV-1 and -2) were investigated by using a yield reduction assay. Ketoconazole demonstrated antiviral activity against HSV-1 and -2 and synergistic antiviral activity when it was combined with acyclovir. Combinations of ketoconazole with adenine arabinoside resulted in either interference or indifference. The effects of ketoconazole upon the protein synthesis of HSV-2-infected cells were also determined in an effort to define the mechanism of action for the antiviral activity of ketoconazole. There was no reduction of HSV proteins when compared with acyclovir. These findings suggest that further investigations of the use of ketoconazole for the treatment of HSV infections are warranted.